"The effect of using the interactive board on reading comprehension among fifth grade pupils. (Journal of the College of Basic Education, 2022)
The importance of the current research is that it came as a result of what societg calls at the present time to search for the most appropriate modern methods and teaching models to communicate in formation to students and to make a significant increase in accumulated knowledge and concepts,so it is necessary to create modern strategies that stimulate the learners thinking and make it effective in the educational process in this way . the interactive whiteboard that works to organize ideas and meanings and clarifies the relationships between concepts that in clude asubject from the established curriculum . this research aims to know the effect of using the inter active board on reading comprehension for fifth grade primary students .the researcher chose the design for the brothe white partial control and the duration consisted of (62)students of the fifth grade elementary students in lbn zaydoon school for boys which is affiliated to the second rusafa education directorate in Baghdad,it was distributed to two groups of (31) pupils in the experimental group and (31)pupils in the control group, the researcher studied the pupils of the experimental group using the interactive board and studied group pupils,the control is the same substance as usual. The researcher rewards among the students of the two study groups statistically in the variables(time age calculated in months-academic achievement for parents-grades of Arabic language for the previous academic year 2018-2019 as well as intelligence using the (Raven test). The researcher prepared teaching plans for reading topics that were studied in the experiment in the light of the books content for the first semester and identified eight subjects from the subjects, to be taught for the a academic year 2019-2020 AD by the ministry of Education for the fifth grade of primary school that you study during the experiment and for the purpose of measuring the level of reading comprehension at students of the two research groups, the researcher prepared the reading comprehension test and decided to choose a reading piece from the reading book to be taught for the fifth grade of primary education and its title (Canadian and the son of the sick merchant) page (15-17). Test paragraphs (30). Elective in six questions, as the first question was a multiple choice, the second and third questions are pairing the fourth question is complementarity and the fifth question is knowing the meaning of the word and the sixth question rearranging the sentence. Using the T-test for two independent samples that resulted in the search for the following result, there is a statistically significant difference at the level of significance (0,05)between the average scores of students of the experimental group who studied the reading subject using the interactive board and the degrees of students of the control group who studied the same material in the usual way and in favor of the experimental group, the difficulty Levey, the ease of its paragraphs, the strength of its distinction and the effectiveness of the mistake alternatives were calculated, and in light of the result reached by the researcher recommends the following:- 1-Adopting the interactive whiteboard to be effective in teaching reading for fifth grade primary school students. 2-Organizing training courses for teachers on the interactive whiteboard applying them in teaching Arabic reading. 3-The necessity of educational supervisors to emphasize the importance whiteboard in teaching during their field visits to teachers of Arabic language subject matter. To complement the a aspects of the current research the researcher suggests the following:-1- Conducting a study similar to the current study dealing with reading comprehension in other academic stages. 2-Conducting a pilot study aimed at identifying the effectiveness of the interactive white board in reading comprehension. 3-Conducting a similar study to identify the effect of using the interactive whiteboard in other branches of the Arabic language such as grammar rhetoric, literature , expression spelling criticism .